2017
DOI: 10.5852/ejt.2017.275
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Nassarius pauperus (Gould, 1850) complex (Nassariidae): Part 3, reinstatement of the genus Reticunassa, with the description of six new species

Abstract: D N A L i b r a r y o f L i f e , r e s e a r c h a r t i c l eurn:lsid:zoobank.org:pub:FC663FAD-BCCB-4423-8952-87E93B14DEEA Abstract. In this review (third part), several species within the Nassarius pauperus complex from the eastern Indian Ocean and western Pacific are treated, including a revised concept of Nassa paupera Gould, 1850, type species of the genus Reticunassa Iredale, 1936. In the most recent taxonomic revision, several species had been synonymized with Nassarius pauperus (Gould, 1850), despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 808 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The intraspecific K2P COI divergences in the three putative species ranged from 0 to 1.82%, whereas the interspecific COI divergences ranged from 3.74 to 7.17%. These results are consistent with those for other Neogastropoda (particularly Nassariidae) that have intraspecific COI divergences ranging from 0 to 3.00% and interspecific COI divergences ranging from 2.10 to 19.80% (Zou et al 2011; Galindo et al 2017; Nerurkar et al 2020). As a result, the levels of sequence divergence among the three putative species are approximately comparable to species-level divergences in other neogastropod and nassariid genera.…”
Section: Systematicssupporting
confidence: 90%
“…The intraspecific K2P COI divergences in the three putative species ranged from 0 to 1.82%, whereas the interspecific COI divergences ranged from 3.74 to 7.17%. These results are consistent with those for other Neogastropoda (particularly Nassariidae) that have intraspecific COI divergences ranging from 0 to 3.00% and interspecific COI divergences ranging from 2.10 to 19.80% (Zou et al 2011; Galindo et al 2017; Nerurkar et al 2020). As a result, the levels of sequence divergence among the three putative species are approximately comparable to species-level divergences in other neogastropod and nassariid genera.…”
Section: Systematicssupporting
confidence: 90%
“…The reconstructed phylogeny of Galindo et al (2016) showed that the cosmopolitan subfamily Nassariinae comprises about 80% of nassariid species diversity (MolluscaBase, 2020a). Up to five strongly supported clades were recovered within this subfamily and were assigned to genera with relatively distinct geographical distributions: the Indo-Pacific Nassarius and Reticunassa (the "pauper-complex" sensu Kool & Dekker, 2006, Galindo, Kool, & Dekker, 2017; the mostly Atlantic-Mediterranean Tritia; the (East and West) African Naytia; and the Caribbean-Panamanian Phrontis. Furthermore, these genera showed different types of protoconch.…”
Section: Introductionmentioning
confidence: 99%
“…Couceiro et al [ 17 ] used the COI gene to distinguish between the two morphologically similar species, Nassarius nitidus and Nassarius reticulatus , which showed a clear barcoding gap. Using COI and 28S rDNA , Galindo et al [ 32 ] analyzed the Nassarius pauperus complex from the eastern Indian Ocean and western Pacific Ocean, including a revised concept of Nassa paupera Gould, 1850, type species of the genus Reticunassa Iredale, 1936, and discovered six new species. Lobo et al [ 53 ] pointed out that some of the so-called “universal primers” still failed to amplify COI-5P in some marine animal groups.…”
Section: Dna Barcoding Is Widely Used In Toxic Marine Algae and Mementioning
confidence: 99%